Flight Operation Officer (FOO) Perception Of The Effectiveness Of The Integrated Operations Control Center (IOCC) On Airlines - Dimas Dicky; Dede Adrian; Kukuh Tri; Lubis, Marsel (FTK UNSURYA, 2025)
The implementation of the Integrated Operations Control Center (IOCC) is an airline operational innovation to create a more integrated and responsive system. In this context, the Flight Operation Officer (FOO) plays a strategic role in designing and overseeing flight operations. The purpose of this study was to determine the extent to which the FOO's perceptions influence the effectiveness of the IOCC in supporting airline operations. Using a descriptive quantitative approach, data were obtained through a survey of 20 active FOOs using a Likert-based questionnaire, then analyzed using descriptive statistics and simple linear regression. The results showed that the FOO's perceptions of the IOCC tended to be positive, with the coordination aspect receiving the highest rating. Regression tests revealed a significant influence between the FOO's perceptions and system effectiveness (p < 0.05; R² = 0.62). These findings indicate that the effectiveness of the IOCC depends not only on the technological aspect, but also on user involvement and perspectives. Therefore, strengthening cross-functional training and improving the internal communication system are important steps to support the FOO's role in optimally implementing integrated operations.